Resepsi Perempuan terhadap Komentar atas Perempuan di Youtube - Tri Indah Lestari; Holy Rafika Dhona (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
Gita Savitri Devi's Youtube channel often discusses women's issues, one of which is entitled "Equal? Women are still victims of sexism!" the comments on the video contain not only expression comments but also sexism, but some women do not realize the existence of sexism comments because of their common understanding of it. Through descriptive qualitative research with a netnographic approach and collecting several data through in-depth interviews with Gita Savitri Devi fans and using the concept of texture and reception, the researchers got several findings where the reception of women in comments on Youtube is a space of expression. The meaning of comments by women towards expression comments is in the dominant hegemonic reading and the negotiated reading, while sexism comments are in the negotiated and opposed reading. Women stated that the image of women in the comments was quite in line with the picture of real life or experiences that women had experienced.